The relationship between the speed of the ball and precision in the flat service in development tennis players - R. Menayo; J.P. Fuentes; F. J. Moreno; R. Clemente; T. García Calvo (Asociación Española de Ciencias del Deporte, 2010)
Speed-accuracy tradeoff has been investigated in the execution of different motor skills. These variables seem to be very relevant to the performance of tennis service. In this study the effects of ball speed modification regarding the accuracy of the flat service have been investigated. 21 players got two conditions for implementation. Each one made 80 hits, 40 at maximum power and 40 to minimum power. The accuracy was recorded depending on the shot area and was lower as the trials were farest from the 4 confined areas in the service box. The results show significant differences  between the hits made to minimum and maximum power, as well as a significant  and negative correlation among services at minimum power and the score of them. Key Words: tennis, service, speed, accuracy.